In Vitro Evaluation of Colloidal Silver on Immune Function: Antilymphoproliferative Activity - Franco Molina, Moisés Armides; Mendoza Gamboa, Edgar; Zárate Triviño, Diana Ginette; Coronado Cerda, Erika Evangelina; Alcocer González, Juan Manuel; Reséndez Pérez, Diana; Rodríguez Salazar, María del Carmen; Rivera Morales, Lydia Guadalupe; Tamez Guerra, Reyes Silvestre; Rodríguez Padilla, María Cristina (Hindawi Publishing Corporation, 2016)
Colloidal silver (AgC) is currently used by humans and it can be internalized through inhalation, injection, ingestion, and dermal contact. However, there is limited information about immunological activity; more investigations using colloidal silver are needed. In the present study, the effects of AgC (17.5 ng/mL) on immunological parameters (proliferation and immunophenotyping) using human peripheral blood mononuclear cells (PBMC) and macrophages (phagocytosis) and cytotoxicity on leukemia and lymphoma cancer cell lines (1.75 to 17.5 ng/mL) were investigated. AgC was observed to significantly (p<0.05) decrease interleukin-2 (IL-2) production and proliferation induced by phytohemagglutinin or concanavalin A in PBMC without affecting its cell viability but with cytotoxic effect on cancer cells. IL-2, IL-4, IL-6, IL-10, INF-γ, and IL-17A cytokines production and CD3+, CD3−CD19+, CD3+CD4+, CD3+CD8+, and CD16+CD56+ PBMC phenotypes were not affected by AgC. The present study demonstrates that colloidal silver is harmless and nontoxic to the immune system cells and its ability to interfere with the immune response by decreasing cell proliferation when stimulated with mitogens demonstrated the antilymphoproliferative potential of AgC.